Encephalitozoon cuniculi in Raw Cow's Milk Remains Infectious After Pasteurization - Kváč, Martin; Tomanová, Vendula; Samková, Eva; Koubová, Jana; Kotková, Michaela; Hlásková, Lenka; McEvoy, John; Sak, Bohumil (Foodborne pathogens and disease, 2016)
This study describes the prevalence of Encephalitozoon cuniculi in raw cow's milk and evaluates the effect of different milk pasteurization treatments on E. cuniculi infectivity for severe combined immunodeficient (SCID) mice. Using a nested polymerase chain reaction approach, 1 of 50 milking cows was found to repeatedly shed E. cuniculi in its feces and milk. Under experimental conditions, E. cuniculi spores in milk remained infective for SCID mice following pasteurization treatments at 72 °C for 15 s or 85 °C for 5 s. Based on these findings, pasteurized cow's milk should be considered a potential source of E. cuniculi infection in humans.
Keywords: Cattle; Feces; polymerázová řetězová reakce; Mice, SCID; skot; Spores, Fungal; pasterizace; spory hub; Animals; Encephalitozoon cuniculi; ženské pohlaví; zvířata; myši SCID; mléko; vysoká teplota; myši; Polymerase Chain Reaction; Mice; Female; Pasteurization; feces; Hot Temperature; Milk